Tingkat pengetahuan, sikap dengan perilaku pencegahan penularan HIV/AIDS pada penderita HIV/AIDS di RSUD Dr Moewardi Surakarta - Iyeti Listyorini; Yuni Kusmiyati; Margono Margono (Jurnal Kesehatan Ibu dan Anak, 2012)
HIV/AIDS is a disease which causes by the Human immunodeficiency virus (HIV) with rapid deployment. WHO declared HIV/AIDS as a pandemic that could threaten the sustainability of mankind. The number of people with AIDS in Indonesia in 2011 as many as 24,482 patients with the number of patients mortality is 18%. Businesses that are not beneficial to avoid the spread of HIV/AIDS prevention. Less accurate information and knowledge about the transmission of HIV/AIDS is one of the high transmission of HIV/AIDS. Efforts to prevent HIV/AIDS is highly dependent on knowledge and attitudes, behavior and other factors involved. Objectives to Know the relationship between the level of knowledge and altitudes with the behavior of HIV/AIDS prevention in people with HIV/AIDS at the Dr. MoewardiSurakada Hospitalin 2011. The type of study is an analytical survey with a cross-sectional/ research design. Samplestakenlrom HIV/AIDS sufferer at the hospital of Dr. Moewardi Surakada with purposive sampling. The analysis using the R Commander Pearson Product Moment Correlation Test. Result: Most of the respondents have a good knowledge level that is equal to 85,9%. All respondents have a positive attitude and 50% have good behavior. P-Value of Pearson Product Moment Test between the level of knowledge and behavior is 0,0387, and between attitude and behavior is 0.005624.